2012
DOI: 10.1108/09564231211269801
|View full text |Cite
|
Sign up to set email alerts
|

How organizational and employee‐customer identification, and customer orientation affect job engagement

Abstract: PurposeThe purpose of this paper is to examine the impact of organizational and employee‐customer identification on job engagement. The paper also aims to explore the role of customer orientation in the model as a consequence of identification, in addition to an antecedent of engagement.Design/methodology/approachThis study utilizes an online survey administered to Cooperative Extension employees in frontline service roles. Amos 18.0 was employed to examine the proposed structural model.FindingsThis study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 66 publications
4
82
1
1
Order By: Relevance
“…This provides drive and motivation and increases overall employee engagement and improved career choices. The results of this study substantiate the hypothesis that customer orientation has significant relationship with career satisfaction (Lounsbury, Loveland et al 2003) and job engagement (Anaza and Rutherford 2012); (Zablah, Franke et al 2012).Sixth hypothesis anticipated that CO has a partial mediating impact on JR and job engagement. Since other variables that possibly affect the relationship between JR and job engagement, and other aspects of relationship marketing were not considered, partial mediation and limited significance of the indirect relationship was established.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…This provides drive and motivation and increases overall employee engagement and improved career choices. The results of this study substantiate the hypothesis that customer orientation has significant relationship with career satisfaction (Lounsbury, Loveland et al 2003) and job engagement (Anaza and Rutherford 2012); (Zablah, Franke et al 2012).Sixth hypothesis anticipated that CO has a partial mediating impact on JR and job engagement. Since other variables that possibly affect the relationship between JR and job engagement, and other aspects of relationship marketing were not considered, partial mediation and limited significance of the indirect relationship was established.…”
Section: Methodssupporting
confidence: 80%
“…Their performance in handling customers' issues is superior as compare to anything those with low customer orientation. Anaza and Rutherford (2012)and Zablah, Franke et al (2012)found customer orientation as an antecedent of engagement. On the basis of this discussion, it is hypothesized that H4: CO has a positive relationship with job engagement.…”
Section: Customer Orientation and Job Engagementmentioning
confidence: 99%
“…At the employee level, ECO has been described as a psychological phenomenon antecedent to important job states (Matsuo, 2011;Donavan et al, 2004;Anaza & Rutherford, 2012), or as frontline employee behaviors that are caused by job states or perceptions of organizational characteristics (e.g. Saxe & Weitz, 1982;Rozell, Pettijohn & Parker, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…And third, we have evidence that customer orientation can affect employee engagement (e.g. Anaza & Rutherford 2012), and thus a supplier's key internal resource base, its human capital resources (Barney 1991;Kumar & Pansari 2015. To motivate a firm's human capital basis is highly important, considering also that employee engagement has in turn been found to impact customer engagement, and consequently firm performance (Harmeling et al 2017;Pansari & Kumar 2017).…”
Section: Customer Orientationmentioning
confidence: 97%
“…), we anticipate that a customer's perception of the supplier's product innovativeness is a relevant aspect of relationship quality (Ford 1980;Dorsch et al 1998). Furthermore, we expect that raising relationship quality a nd perceived customer participation may not only impact employee engagement (Anaza et al 2012;, but also entice the customer to allocate a greater share of its purchases to a given focal supplier. In the absence of empirical evidence on how perceived innovativeness relates to retention or performance, we conjecture once more from Anderson et al (2000) and its adaptation to SWO that the innovativeness-SOW link is also likely non-linear with increasing returns, as for the satisfaction-behavior link (Mittal et al 2001).…”
Section: Perceived Product Innovativenessmentioning
confidence: 99%